Strategi Dan Policy Manajemen Untuk Menerjemahkan Aktivitas Pengadaan Material Dan Forecasting Material : Laporan Kegiatan Kuliah Kerja Lapangan - Zainul Arifudin; Achmad Daengs GS; Rina Dewi; Diana Zuhro; Sutini Sutini (Jurnal Pengabdian Masyarakat, 2024)
This section presents order growth projections based on professional analyst consensus estimates to help analyze procurement orders in the inventory control section. Inventory control in a company is closely related to the activity of collecting data about activities and transactions in and out of a company's goods. The basic concept of inventory is that every company, whether it is a trading company or factory company or service company, always holds inventory. Without inventory, entrepreneurs will be faced with the risk that their company at some point will not be able to fulfill the desires of customers who need or request goods/services. Inventory is held if the expected profit from the inventory should be greater than the costs it incurs. By designing a better system, it is hoped that it can help and facilitate the ongoing system process, making it easier to process data, including processing, compiling, storing and manipulating data, which ultimately produces accurate data that can be used for company needs. For this reason, an information system is needed to overcome this problem, a dual information system that can inform existing data correctly and accurately.